Prevalence, resistance patterns, and risk factors for antimicrobial resistance in bacteria from retail chicken meat in Colombia - Donado-Godoy, Pilar (2015)
As a step toward implementing the Colombian Integrated Program for Antimicrobial Resistance Surveillance (COIPARS), this study aimed to establish the baseline antimicrobial resistance patterns of Salmonella serovars, Escherichia coli, and Enterococcus spp. isolates in retail poultry meat from independent stores and from a main chain distributor center. MICs of the isolates were determined for antimicrobials used both in humans and animals, using an automated system. Salmonella serovars were isolated from 26% of the meat samples and E. coli from 83%, whereas Enterococcus faecalis and Enterococcus faecium were detected in 81 and 13% of the meat samples, respectively. A principal finding of concern in this study was that almost 98% of isolates tested were multidrug resistant. Ceftiofur, enrofloxacin, nalidixic acid, and tetracycline were the antimicrobials that showed the highest frequency of resistance among Salmonella and E. coli isolates. For enterococci, 61.5% of E. faecium isolates were found to be resistant to quinupristin-dalfopristin; this is significant because it is used to treat nosocomial infections when vancomycin resistance is present. Vancomycin resistance was detected in 4% of the E. faecalis isolates. The results of our study highlight the need for rapid implementation of an integrated program for surveillance of antimicrobial resistance by the Colombian authorities in order to monitor trends, raise awareness, and help promote practices to safeguard later generation antimicrobial agents.